Growth of motorcycle use in Metro Manila impact on road safety. - Asian Development Bank. (Metro Manila, Philippines Asian Development Bank, 2020)
This study analyzes the use of motorcycles in Metro Manila with the aim of informing government policy related to road safety and transport planning. Motorcycles are increasingly being used for daily commutes as well to provide logistics services. The study explores the various drivers, characteristics, and implications of increased motorcycle use. Taking into account these implications, it presents a policy framework to reduce motorcycle-related crashes and suggests that the Public Service Act be reviewed and amended as appropriate to recognize motorcycles as a primary mode of transport.
Keywords: Motorcycles -- Philippines -- Manila Metropolitan Area; Motorcycles -- Safety measures; Electronic books